A novel retrieval-dependent memory process revealed by the arrest of ERK1/2 activation in the basolateral amygdala - Merlo, Emiliano (2018)
Fully consolidated fear memories can be maintained or inhibited by retrieval-dependent mechanisms depending on the degree of re-exposure to fear cues. Short exposures promote memory maintenance through reconsolidation, and long exposures promote inhibition through extinction. Little is known about the neural mechanisms by which increasing cue exposure overrides reconsolidation and instead triggers extinction. Using auditory fear conditioning in male rats, we analyzed the role of a molecular mechanism common to reconsolidation and extinction of fear, ERK1/2 activation within the basolateral amygdala (BLA), after intermediate conditioned stimulus (CS) exposure events. We show that an intermediate re-exposure (four CS presentations) failed to activate ERK1/2 in the BLA, suggesting the absence of reconsolidation or extinction mechanisms. Supporting this hypothesis, pharmacologically inhibiting the BLA ERK1/2-dependent signaling pathway in conjunction with four CS presentations had no effect on fear expression, and the NMDA receptor partial agonist D-cycloserine, which enhanced extinction and ERK1/2 activation in partial extinction protocols (seven CSs), had no behavioral or molecular effect when given in association with four CS presentations. These molecular and behavioral data reveal a novel retrieval-dependent memory phase occurring along the transition between conditioned fear maintenance and inhibition. CS-dependent molecular events in the BLA may arrest reconsolidation intracellular signaling mechanism in an extinction-independent manner. These findings are critical for understanding the molecular underpinnings of fear memory persistence after retrieval both in health and disease.